PENGUNGKAPAN DIRI PADA REMAJA DENGAN MENGGUNAKAN JEJARING SOSIAL FACEBOOK - Muhammad Fathul Huda (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2020)
AbstractThis research is motivated use of the internet, especially in his own country Indonesia. And also important to know how the relationship between the Adolescents and social networking facebook. Because most of social networking users in Indonesia are Adolescents. In fact, a survey conducted by the Ministry of Communication and Information of the Republic Indonesia confirmed that their. The phenomenon of adolescents using social networking is very interesting to study. By using the Social Network adolescents ventured to form their social identity. That is by disclosure a personal thing to others, or even before the public. There are many theories of communication that support for such research, among which Self-disclosure Theory, Communication Privacy Management (CPM), and Social Exchange Theories. Therefore, researchers here will focus on research aimed at finding out the causes of self-disclosure in adolescents using social networking facebook (Case Studies of Students SMK Al-Fata on Village Billapora Rebba Sub-District Lenteng District Sumenep). The research method used was a case study approach to the type of form of qualitative research. The data collection techniques through documentation, interviews, and observation as supporting. The subjects were all students of SMK Al-Fata. Mechanical analysis of data collected is the data reduction, data display, and conclusion drawing. As for checking the validity of the data the researchers used a technique of observation extension, increase persistence and triangulation. Results from this research is the first that became the background of self-disclosure to the students of SMK Al-Fata them because it is easier and daring, because the feeling is not revealed, because of limited entertainment, and because it takes a friend to chat. The second function of self-disclosure to the students of SMK Al-Fata them to alleviate the problem, to encourage reciprocation, and to share experiences. Key words : Self-disclosure, Adolescent, Social Network